2021
DOI: 10.3389/fcvm.2021.750573
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging in the Diagnosis of Prosthetic Valve Endocarditis: A Brief Review

Abstract: Infective endocarditis is a common and treatable condition that carries a high mortality rate. Currently the workup of infective endocarditis relies on the integration of clinical, microbiological and echocardiographic data through the use of the modified Duke criteria (MDC). However, in cases of prosthetic valve endocarditis (PVE) echocardiography can be normal or non-diagnostic in a high proportion of cases leading to decreased sensitivity for the MDC. Evolving multimodality imaging techniques including leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Particularly, the results of this study will also evaluate the role and value of multimodal imaging in the diagnosis of endocarditis in the contemporary era. The increased sensitivity in the diagnosis afforded by more advanced imaging techniques and more widespread availability of multimodality imaging 25 may help address some of the current challenges in the management of endocarditis and will attempt to address some key questions, such as optimal timing and frequency for follow-up imaging. Current ESC guidelines recommend transthoracic echocardiographic imaging at the end of the antibiotic therapy to define the final degree of valve disease after endocarditis and presence or sizes of residual vegetations 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the results of this study will also evaluate the role and value of multimodal imaging in the diagnosis of endocarditis in the contemporary era. The increased sensitivity in the diagnosis afforded by more advanced imaging techniques and more widespread availability of multimodality imaging 25 may help address some of the current challenges in the management of endocarditis and will attempt to address some key questions, such as optimal timing and frequency for follow-up imaging. Current ESC guidelines recommend transthoracic echocardiographic imaging at the end of the antibiotic therapy to define the final degree of valve disease after endocarditis and presence or sizes of residual vegetations 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Combined, these criteria provide a diagnostic probability defining cases as definite, possible, or rejected [13]. Studies have confirmed the high sensitivity and specificity of the modified Duke criteria for identifying definite cases of IE [14][15][16][17][18][19][20][21][22][23][24][25]. However, it should be noted that extending these criteria to infections related to prosthetic valves, indwelling cardiac devices, and endocarditis of the right-heart yields significantly inferior sensitivity [1,26].…”
Section: Evaluation and Diagnosismentioning
confidence: 96%
“…Indeed, the European and American guidelines primarily focus on the role of cerebral magnetic resonance imaging (MRI) and its significance in identifying cerebrovascular emboli. They briefly acknowledge CMR as a new imaging tool that could be incorporated into the diagnostic algorithm [5,9,39,40].…”
Section: Evidencementioning
confidence: 99%
“…Despite concern over the infection risk associated with contrast agents and MRI's relative limitations in patients with existing metallic prostheses, CMR may provide superior evaluation of transvalvular flows when utilising 2D PCI flows or 4D flow, which is especially useful in the assessment of valve regurgitation due to perforation or destruction of the cusps or due to paravalvular leakage. Furthermore, in complex haemodynamic scenarios, such as assessment of intracardiac fistula, CMR can be used to more accurately quantify the shunt using 2D PCI flow sequences [36,40]. In terms of accurate diagnosis, CMR with LGE may assist in identifying myocarditis, an important immune-mediated differential of infective endocarditis.…”
Section: Evidencementioning
confidence: 99%